1988
DOI: 10.1021/bi00418a053
|View full text |Cite
|
Sign up to set email alerts
|

Subunit arrangement in beef heart complex III

Abstract: Beef heart mitochondrial complex III was separated into 12 polypeptide bands representing 11 different subunits by using the electrophoresis conditions described by Schägger et al. [(1986) Methods Enzymol. 126, 224-237]. Eight of the 12 polypeptide bands were identified from their NH2-terminal sequences as obtained by electroblotting directly from the NaDodSO4-polyacrylamide gel onto a solid support. The topology of the subunits in complex III was explored by three different approaches. (1) Protease digestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(58 citation statements)
references
References 60 publications
4
53
1
Order By: Relevance
“…This would lead to a decrease of the bc1 complex activity at high temperature, as in the ⌬qcr9 mutant. Previous studies have shown that Qcr9p interacts with Rieske and cytochrome c1 (5,9,35), therefore we propose that Qcr9p could enhance or stabilize the interactions between these two catalytic subunits. It was previously shown that in the total absence of Qcr9p, the conformation of Rieske and its iron-sulfur cluster insertion is altered (9).…”
Section: Discussionmentioning
confidence: 69%
“…This would lead to a decrease of the bc1 complex activity at high temperature, as in the ⌬qcr9 mutant. Previous studies have shown that Qcr9p interacts with Rieske and cytochrome c1 (5,9,35), therefore we propose that Qcr9p could enhance or stabilize the interactions between these two catalytic subunits. It was previously shown that in the total absence of Qcr9p, the conformation of Rieske and its iron-sulfur cluster insertion is altered (9).…”
Section: Discussionmentioning
confidence: 69%
“…Apparent molecular masses were calculated based on the reported molecular masses of bovine cytochrome c oxidase (24). Immunoblotting was carried out as in Gonzá lez-Halphen et al (25). Antibodies against yeast COX III were obtained from Molecular Probes (Eugene, Oregon).…”
Section: Methodsmentioning
confidence: 99%
“…Antibodies were raised in rabbits injected with purified yeast GDH1-encoded NADP-GDH and partially purified by ammonium sulfate precipitation according to the method of Gonzá lez-Halphen et al (26).…”
Section: Preparation Of Anti-nadp-gdh Antibodiesmentioning
confidence: 99%